Analisa Kinerja Jaringan Peer-to-Peer (P2P) BitTorrent - Vernata, Wan Delkey; Febrizal, Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Since its creation by Bram Cohen in 2001, BitTorrent has proven to provide the best way to file distribution among peer-to-peer system. Instead of establishing a single one-way stream of information like a client-server system, BitTorrent makes several connections to other clients that contain at least part of the desired information. This information is then simultaneously downloaded from and uploaded to the other clients in pieces. To design a close-to-real-world testing environment for BitTorrent experiment at the costs of a real hardware solution in this paper presents a BitTorrent performance analysis with virtualization. From results of the experiment suggested BitTorrent get faster distribution time compared to FTP with more requests and can be slower if have to deal with free riders clients. At the piece selection experiment, suggested BiTorrent get best distribution time at piece with numbers 1400.Keyword: Peer-to-Peer, BitTorrent, Virtualisation, Performance Analisys